SOSIALISASI MODUL PELATIHAN SUMBER DAYA MANUSIA UNTUK PENGEMBANGAN WISATA DESA MEKARBUANA KECAMATAN TEGALWARU KABUPATEN KARAWANG - Budi Rismayadi; Wike Pertiwi (SOCIRCLE : Journal Of Social Community Services, 2023)
The aim, benefits and impact of this socialization aims to provide understanding to Pokdarwis, Bumdes and the Mekarbuana village community to always work together in developing tourism even though there has been no assistance from any party. The final impact of this tourism development is the welfare of the community.